2003
DOI: 10.3168/jds.s0022-0302(03)73642-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abomasal Infusion of Conjugated Linoleic Acid on Milk Fat Concentration and Yield from Pasture-Fed Dairy Cows

Abstract: The aim of this study was to investigate the effects of conjugated linoleic acid supplementation on the synthesis of milk fat in pasture-fed Friesian cows. In four cows, a commercial mixture containing 62.3% (wt/vol) conjugated linoleic acid was infused intraabomasally to avoid rumen fermentation and biohydrogenation. The design was a 4 x 4 Latin square in which each cow received infusions of 0, 20, 40, and 80 g/d of conjugated linoleic acid mixture for 4 d. Cows were fed freshly cut ryegrass/white clover past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
78
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 13 publications
24
78
6
1
Order By: Relevance
“…In dairy cows, the decrease in the MFC and in the fat yield were largely related to a decrease in the yield and in the percentage of shortto medium chain saturated FA [2]. The highest decreases in short to medium-chain saturated FA were observed with the highest doses of t10,c12-C18:2 infused [7,8,26]. However, in our trial no effect on MFC was observed whatever the diet, probably because the synthesis of even-numbered saturated FA with 4 to 16 C was not decreased despite a high t10,c12-C18:2 concentration in milk fat.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In dairy cows, the decrease in the MFC and in the fat yield were largely related to a decrease in the yield and in the percentage of shortto medium chain saturated FA [2]. The highest decreases in short to medium-chain saturated FA were observed with the highest doses of t10,c12-C18:2 infused [7,8,26]. However, in our trial no effect on MFC was observed whatever the diet, probably because the synthesis of even-numbered saturated FA with 4 to 16 C was not decreased despite a high t10,c12-C18:2 concentration in milk fat.…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, product to substrate ratios of c9-C14:1/C14:0, c9-C16:1/C16:0, c9-C18:1/C18:0, and c9,t11-C18:2/t11-C18:1 represent a desaturase index and they serve as a proxy for Δ 9 desaturase activity. In dairy cows, the infusion of a high dose [7,16,26] but not of a low dose [7,8,25] of t10,c12-C18:2 reduced desaturase indexes in milk fat. Baumgard et al [16] demonstrated that the mechanism by which t10,c12-C18:2 decreased these substrate to product ratios involves a reduction in the mRNA abundance of Δ 9 desaturase in the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain marketing systems and management schemes, it may be advantageous to reduce milk fat yield , and in some feeding and management systems the reduction in milk fat yield has allowed for a repartitioning of nutrients to support increased milk and milk protein yield (e.g. Bernal-Santos et al, 2003;Mackle et al, 2003;Lock et al, 2006b;Odens et al, 2007). Producers may also find it advantageous to induce MFD during periods of limited feedstuff availability such as inadequate rainfall in pasture-based systems or for a short period while breeding.…”
Section: Insights Gained From Milk Fat Depressionmentioning
confidence: 99%
“…In a previous study using the same source of cSFA fed to grazing cows, milkfat concentration was reduced (-26% in respect to the Control group) with no negative effect on NDF digestion (Schroeder et al 2003). In pasture-fed MC, milkfat concentration was decreased 43% by the abomasal infusion with 40 g day -1 of a clA mixture, reducing the energy requirements for lactation (13%) and increasing milk yield (11%; Mackle et al 2003).…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Consequently, a reduction of milkfat synthesis by unsaturated FA supplementation may be potentially beneficial to grazing dairy cows in early lactation, increasing milk production or enhancing the energy balance of the cow (Mackle et al 2003). Thus, supplementing unsaturated FA may not only increase energy density in pasture-based diets but also reduce milkfat concentration, diverting energy to milk yield and/or body reserves recovery.…”
Section: Introductionmentioning
confidence: 99%